THE EFFECT OF TURMERIC EXTRACT (Curcuma longa) ON THE IMPROVEMENT OF MUSCLE MASS IN SWISS DIABETES MELITUS MICE SKELETAL MUSCLE INDUCED BY STREPTOZOTOCIN - Alfin Ihza Trimahendra; Yora Nindita; Vega Karlowee; Muhamad Thohar Arifin; Mochamad Ali Sobirin (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Backgrounds. Diabetes mellitus is a degenerative disease that has various complications. One of neglected diabetes mellitus complication is skeletal muscle atrophy. Turmeric and java turmeric extracts were need to be clarified due to those effect as antihyperglycemic agent which might affected muscle atrophy as one of diabetes mellitus complication. Aim. To compared the efficacy of turmeric and java turmeric extract on reducing the progression of skeletal muscle atrophy in streptozotocin-induced diabetes mellitus. Methods. We conducted experimental animal studies with a post test only control group design using 25-30 grams male Swiss mice aged 12 weeks. Diabetes mellitus was induced by streptozotocin (STZ) administration. All 28 samples were randomly divided into 4 groups : control + PBS, control + STZ, STZ + turmeric, and STZ + java turmeric groups. Before treatment, blood glucose and body weight were examined on 3rd day. Blood glucose, body weight, hindlimb muscle weight, and muscle diameter results were examined after treatment (on 21st day). Data was analyzed with statistical software after all procedures were done. Results. STZ + turmeric group showed insignificant decreased in blood sugar levels (p=0.107). Control + STZ group showed significantly reduced hindlimb muscle weight compared to other groups. Hindlimb muscle weight was significantly ameliorated by STZ + turmeric extract (p=0.048). There were no significant improvement on skeletal muscle diameter among groups. Conclusion. The administration of turmeric extract improved hindlimb muscle weight but may not mediated by glucose lowering effect in streptozotocin induced diabetic mice.